Palm Oil Mill Effluent Biochar as An Alternative Potassium Source: Effect of Pyrolysis Time and Its Kinetic Release - Krisnanti, Gendis Yayi; Gusrizal, Gusrizal; Wahyuni, Nelly (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2024)
Palm Oil Mill Effluent (POME) is one of the waste products of palm oil processing that can be processed into a biochar. POME biochar contains high levels of nutrient, such as NPK which can be used an alternative potassium source material. This study aims to produced biochar from POME and the influence of pyrolysis time on the characteristics and its kinetic release. Biochar production from POME was conducted at 300oC with pyrolysis time variation of 1 hour, 3 hours and 5 hours. Biochar characterization was conducted using Fourier Transform Infrared (FTIR) Spectroscopy, Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX), Surface Area Analysis (SAA). Study of potassium release was conducted by mixing one gram amount of biochar with 0.01 M CaCl2 as a function of time. The used kinetics modelling in this study are first-order, second-order, pseudo-first order, pseudo-second orde. The results showed that the biochar yield decreased, while the biochar pH value, exchangeable potassium, non-exchangeable potassium and surface area increased with the increasing of pyrolysis time. The pseudo- second order model is the most fitted model to describe the potassium release. The pseudo-second order kinetics model gave K release rates of 0.018; 0.024; 0.020; 0.014 (mg g-1min-1), the qe values are 0.814; 0.839; 0.927; 1.111 (mg g-1), respectively.